A High Rated Solar Water Distillation Unit for Solar Homes - Abhishek Saxena; Navneet Deval (Journal of Engineering)
India is presently focusing on complete utilization of solar energy and saving fossil fuels, which are limited. Various solar energy systems like solar cookers, solar water heaters, solar lanterns, solar PV lights, and solar lamps are continuously availing by the people of India at a low cost and on good subsidies. Apart from this, India is a solar energy promising country with a good number of solar homes (carrying solar energy systems) in its various locations. The present paper focuses on a unique combination of solar dish cooker (SDC) and solar water heater (SWH) to produce distilled water with a high distillate and a high daily productivity. The procedure has been discussed on the basis of experimental testing to produce distilled water by combining an evacuated type SWH and a SDC. Experimentation has been carried out in MIT, Moradabad (longitude, 28.83°N, and latitude, 78.78°E) by developing the same experimental setup on behalf of solar homes. The daily productivity of distilled water was found around 3.66 litres per day in full sunshine hours for an approximated pH value of 7.7 and a ppm value of 21. The payback period (PBP) has been estimated around 1.16 years of the present system.